A dynamic dual model: The determinants of transnational migrant entrepreneurs' embeddedness in the UK - Rose Quan; Mingyue Fan; Michael Zhang; Huan Sun (Journal of Entrepreneurship, Management and Innovation)
Effective embeddedness in the host country is an important issue for immigrant and transnational entrepreneurs. However, prior research has mainly focused on subsidiaries’ local embeddedness of multinational companies (MNCs). While a limited number of studies have examined transnational enterprises, few have explored how transnational entrepreneurs embed in the host country where they immigrate to. Employing 7 in-depth case studies of Chinese small transnational enterprises operating in the UK, we construct a dynamic dual process model which consists of 3 dimensions: structural embeddedness; institutional embeddedness; and cognitive embeddedness. Our findings make a theoretical contribution by offering insights into how transnational migrant entrepreneurs embed in a dual cross-border business environment.